Maternal physical activity: influence on maternal and delivery outcomes - Watson, Estelle Dorothy (My University, 2016)
Background Physical activity is a potentially powerful tool for addressing the growing concern of non-communicable diseases in low-to-middle income countries. In South Africa, black women are particularly vulnerable to a high prevalence of overweight and obesity as well as low physical activity levels. During pregnancy, the physiological and psychological changes that occur during this unique period may put women at greater risk of being physically inactive and sedentary. Research from high-income countries has shown that, despite the benefits of physical activity during this period, the majority of women do not meet the physical activity recommendations (≥ 150 minutes of moderate physical activity per week), or reduce their activity levels during pregnancy. Several positive associations have been demonstrated between regular physical activity and maternal outcomes, such as improved cardiovascular and strength, as well as a reduced risk of gestational diabetes mellitus, excessive gestational weight gain, gestational hypertension and preeclampsia. Although research indicates the beneficial effects of physical activity during pregnancy on maternal health, controversy still exists regarding its influence on birth outcomes. The theory of metabolic programming provides insight into the potential influence of health behaviours during pregnancy and long term implications for the offspring. Therefore, pregnancy may be a critical time in which to assess, and change, health behaviours that may impact not only the mother, but the next generation as well. Aim Despite the potential role of physical activity in improving maternal health, very little research has been done in a South African context. Therefore, the overall aim of this study is to understand and examine maternal physical activity during pregnancy, and determine its association with maternal and birth outcomes. This thesis is presented as five study components: 1) to provide a theoretical background of evidence examining the role of PA for health during the prenatal period; 2) to examine the attitudes, beliefs and perceived barriers to PA during pregnancy in black South African women; 3) to assess the knowledge, attitudes and beliefs of South African medical practitioners towards exercise prescription during pregnancy; 4) to describe the patterns and correlates of self-reported PA levels during pregnancy in black South African women; and lastly 5) to objectively measure PA at two time points during pregnancy and examine its association with maternal outcomes and birth outcomes. Methods Understanding the attitudes and beliefs of pregnant women and their healthcare providers was done through semi-structured interviews (n=13; 29-33 weeks gestation) and a questionnaire (n=96), respectively. A deductive thematic analysis was done for the qualitative data, based on the Theory of Planned Behaviour. The longitudinal observation of physical activity during pregnancy used both a self-report questionnaire, the Global Physical Activity Questionnaire, as well as a hip-mounted triaxial accelerometer (ActiGraph GT3X+). Physical activity was expressed as MET mins/wk (GPAQ) and gravity-based acceleration units (mg) (accelerometery). Physical activity was measured at two time points during pregnancy namely, 14-18 weeks (GPAQ: n=332; accelerometer, n=120) and 29-33 weeks (GPAQ: n=256; accelerometer: n=90) gestation. Maternal outcomes included both weight and weight change at 29-33 weeks gestation. Birth outcomes included gestational age, birth weight, ponderal index and Apgar score, measured within 48 hours of delivery. Results Semi-structured interviews showed that although the majority of women believed that physical activity was beneficial, this did not appear to translate into behaviour. Reasons for this included pregnancy-related discomforts as well as lack of time, money and physical activity-related education, all of which can contribute to a reduced perceived control to become active. Opportunities to participate in group exercise classes were a commonly reported facilitator for becoming active. In addition, women reported that influential role players, such as family, friends and healthcare providers, as well as cultural beliefs, provided vague, conflicting and often discouraging advice about physical activity during pregnancy. From a health care provider’s perspective, the majority (98% of the medical practitioners) believed that exercise during pregnancy is beneficial, and were knowledgeable on most of the expected benefits. Seventy-eight percent believed that providing exercise advice is an important part of prenatal care, however only 19% provided information pamphlets and few (24%) referred their patients to exercise specialists. A large majority (83%) were unaware of the American College of Obstetrician and Gynaecologists’ recommended exercise guidelines. Although age and years of practice played no role in this awareness, practitioners who focused on obstetrics and gynaecology were more likely to be aware of the current ACOG guidelines, than those in general practice (p<0.001). Both self-reported (GPAQ) and objectively measured (accelerometry) physical activity declined significantly from the second to the third trimester (600 MET mins/wk vs. 480 MET mins/wk; p=0.01 and 12.8±4.1mg vs. 9.7±3.6mg, p=<0.01). Longitudinal data analysis (GPAQ MET mins/wk, n=256) showed that 132 (52%) of the women were active (according to the ACOG guidelines) at 14-18 weeks gestation, and this decreased to 111 (43.4%) at 29-33 weeks gestation. The majority of physical activity time (as measured by the GPAQ) was spent in walking for transport (80%), and less than 2% in recreational activities. In both trimesters, married women were less likely to walk for transport (second trimester: β= -0.12; 95%CI=-0.31,- 0.02, third trimester: β=-0.17; 95%CI=-0.47, -0.07) and women who owned a car were more likely to engage in leisure time PA (second trimester:β= 0.16; 95%CI=0.02-0.32, third trimester: β=0.17; 95%CI=0.04-0.27), but less likely to walk for transport in their second trimester (β= -0.11; 95%CI=-0.31,-0.00). The women reported spending an average of five hours per day sitting (range=180-480minutes). Objectively measured physical activity at 29-33 weeks as well as change in physical activity was inversely associated with gestational weight change at the same time point (β= -0.24; 95%CI= -0.49; -0.00; p=0.05 and β= -0.36; 95%CI= -0.62; -0.10; p=0.01). No significant associations were found between physical activity and birth outcomes. Furthermore, a high prevalence of overweight and obesity in early pregnancy (67.9%, n=332) and self-reported HIV (23.5%, n=332) was found in this population. Conclusion This study provides theoretical insight into the beliefs of urban South African women regarding physical activity during pregnancy. Findings from this study suggest that a holistic approach to improve physical activity compliance during pregnancy is needed, inclusive of physical activity education and exercise opportunities within a community setting. The role of healthcare providers in providing prenatal physical activity counselling should not be underestimated, and our study found that although the medical practitioners were largely positive towards exercise during pregnancy, their advice did not always align with the current guidelines. Therefore, better dissemination of available research is warranted, to bridge the gap between clinical knowledge and current recommendations for physical activity promotion. This is important since our study demonstrated low and declining levels of physical activity during pregnancy in this population, which is of concern. We demonstrated that physical activity during pregnancy may be an effective method to control gestational weight gain, whilst presenting no adverse risk for fetal development, in black South African women from a low-income setting. This is particularly important as most of this population appears to be overweight or obese at the start of their pregnancy. Therefore, interventions that include lifestyle education and provision of accessible recreational physical activity programmes for pregnant women are needed, and this study presents critical formative work upon which these contextually and culturally sensitive interventions can be developed.
A thesis Submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in the fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa